L’avenir du vieux village de Takrouna (Tunisie) : ruines ou emblème de la nouvelle villégiature du Sahel ? - Sonia Fradi; Pierre Donadieu; Hichem Rejeb (Projets de Paysage)
The article describes possible scenarios of evolution of an abandoned Berber village near Sousse in Tunisia. It refers to changes in two other sites of tourist interest, Chebika, near Tozeur and Sidi Bou Said around Tunis. This work is based on surveys of Takrouna villagers, realized when a new international airport was constructed in Hergla few kilometers away.